An analysis of issues and problems of BRAC's Gonokendra Pathagar - Khan, Md. Kaisar Ali; Akter, Shaheen (BRAC Research and Evaluation Division (RED), 2020)
This study aimed at gaining a comprehensive understanding of issues and problems that effect the normal operation of BRAC Gonokendra Pathagar (community based library). Information was collected from six pathagars through in-depth interviews. It was found that community perception towards BRAC Gonokendra Pathagars was positive. The community participated actively in establishing the pathagars that remained active until BRAC contribution was given. The trend of pathagar use gradually increased in the 1 st year of establishment, but declined from the second year. The trend of borrowing books in majority pathagars was found to decline while school examinations became closer and during the long vacations. Predominance of female users was found much higher in the Female type pathagars, but it was lower in the General and Small type pathagars. Almost all the users had interest in newspaper. Reading materials were required in accordance with the level and types of the users, and most users required to have more reference books and religious books. Access of all types of users should be ensured to maximize the utilization of the pathagars. Reading materials should be made available according to their needs and interests. As the normal functioning of the pathagars depends on active committees, careful attention should be given in selecting the committee members to make the pathagar programme more effective and sustainable.